Analisis Rasio Laporan Keuangan PT. Semen Indonesia (Persero) Tbk Untuk Menilai Kinerja Keuangan Perusahaan Tahun 2022 – 2023 - Aysah Putri Cahyani; Choirul Rizki; Denis Nabila Septi; M. Thoha Ainun Najib (Journal Economic Excellence Ibnu Sina, 2024)
This research is aimed at studying and analyzing the financial report ratios of PT. Semen Indonesia (Persero) Tbk to assess the company's financial performance for the 2022-2023 period. Research on PT's financial reports. Semen Indonesia (Persero) Tbk. This is aimed at reviewing and assessing the company's financial performance in the 2022-2023 period. The data was researched and analyzed based on PT's financial reports. Semen Indonesia (Persero) Tbk. In collecting data, researchers used documentation techniques, in the form of secondary data obtained from financial reports. The technical analysis used is technical analysis in the form of a descriptive quantitative approach. The results of this research were obtained from calculations and analysis, starting from the Liquidity Ratio using four formulas, the results obtained were Current Ratio, Quick Ratio, Cash Ratio were not good in 2022 and 2023, while Cash Turn Over was not good in 2022 and was said to be good in 2023 . Solvency formulas using three formulas show that the Debt to Asset Ratio results are both less good in 2022 and 2023, while the Debt to Equity Ratio and Fixed Charge Coverage are said to be good in 2022 and 2023. The Activity Ratio results using five formulas for Total Assets. Turn Over, Fixed Asset Turn Over, Working Capital Turn Over, Inventory Turn Over and Receivable Turn Over are not good in 2022 and 2023. The Profitability Ratio uses three formulas to obtain the results of Return on Equity (ROE), Profit Margin on Sales and Return on Investment (ROI) is not good in 2022 and 2023. Working Capital Turn Over, Fixed Asset Turn Over and Total Asset Turn Over are not good in 2022 and 2023. Profitability Ratios use three formulas to obtain Profit Margin on Sales, Return on Investment (ROI) results ) and Return on Equity (ROE) will not be good in 2022 and 2023.